Residual effect of some nitrogenous fertilizers in corn plant (Zea mays L.) evaluated by dry matter production - Rosales, Manuel Palma; Mello, Francisco A. F.; Arzolla, Sylvio; Thomasi, Maria D. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
An experiment was carried out in pots with four repetitions using an acid soil with poor fertility in order to test the residual values of urea (with and without sulphur), ammonium witate and ammonium sulphate. In the begiming the pH were corrected up to 6,0 and applications of phosphate and potassium fertilizers in quantities of 90 and 120 kg/ha of P(2)0(5) and K(2)0 were respectively done. The quantities of N were 0, 120 and 240 kg/ha. The test plant was corn (Zea mays L.). In the following year this test was repetead, without pH correction and without adding nitrogenous fertilizers. In the subsequent year the same experiment was repeated making, however, pH corrections in two repetitions of each treatment. After havesting the residual effects of the employed fertilizers were studied using the dry matter productions as avaluation parameters. It was concluded that in what concerning the dry matter production of the whole plant and the root-free plant no residual effect of nitrogen was found, except in the corresponding treatments of root-free plants where the pH was not corrected.